Prevalence of the morphological changes of the TMJ observed in panoramic radiographs - Tenorio Estrada, Janet Kely (2019)
Objective: To establish the prevalence of changes in the articulation temporomandibular joint (TMJ) and its association with age, sex, and right side or left side, using panoramic radiographs.  Materials and Methods: We reviewed a total of 360 (720 condyles) x-rays of both sexes and older than 18 years, grouped in three categories, 18 – 40 years, 41 – 60 years and older than 61 years. Will evaluate bone changes of the condyle of the mandible as a subchondral cyst, flattening, erosion, sclerosis and osteophyte.  Results: The prevalence of bone changes of the mandibular condyles was 70,3% being more frequent in the 41-60 years, and in males, finding statistically significant differences. The number of condyles affected was 419 (58.2%). Although both condyles were found affected, for the most part, there were no differences statistically significative on hand. The most common change was flattening and the osteophyte, however, didn´t  find statistically significant differences between the bony changes of the mandibular condyles. Conclusions: The condylar evaluated with panoramic x-ray bone changes arose in the age group of 41-60 years, in the male sex and bilaterally. Panoramic x-ray is an initial resource to study condylar bone changes, which require more specific studies such as Computerized Tomography. In later studies, clinical signs and symptoms should be considered, as well as long-term follow-up.